2020
DOI: 10.1093/conphys/coaa088
|View full text |Cite
|
Sign up to set email alerts
|

In situ and low-cost monitoring of particles falling from freshwater animals: from microplastics to parasites

Abstract: A simple and low-cost method of monitoring and collecting particulate matter detaching from (or interacting with) aquatic animals is described using a novel device based on an airlift pump principle applied to floating cages. The efficiency of the technique in particle collection is demonstrated using polyethylene microspheres interacting with a cyprinid fish (Carassius carassius) and a temporarily parasitic stage (glochidia) of an endangered freshwater mussel (Margaritifera margaritifera) dropping from experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Huber and Geist (2019) have shown that non‐sympatric fishes can be suitable hosts for duck mussel ( Anodonta anatina ), but also, interestingly, found differences in duration of the metamorphosis/ development of glochidia between different host fish species – something that to our knowledge has not yet been studied for the freshwater pearl mussel. Determining metamorphosis success rate and juvenile quality of FPM (see Douda et al., 2020) may yield other new research directions in the area of population‐level host suitability and local adaptation. Finally, as FPM glochidia infestation may provide protection for host fish against bacterial disease (Chowdhury, Roy, et al., 2021), yet unknown features of the co‐evolutionary relationship between endangered FPM and their salmonid hosts – in addition or related to local adaptation – may be recovered through successful conservation programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Huber and Geist (2019) have shown that non‐sympatric fishes can be suitable hosts for duck mussel ( Anodonta anatina ), but also, interestingly, found differences in duration of the metamorphosis/ development of glochidia between different host fish species – something that to our knowledge has not yet been studied for the freshwater pearl mussel. Determining metamorphosis success rate and juvenile quality of FPM (see Douda et al., 2020) may yield other new research directions in the area of population‐level host suitability and local adaptation. Finally, as FPM glochidia infestation may provide protection for host fish against bacterial disease (Chowdhury, Roy, et al., 2021), yet unknown features of the co‐evolutionary relationship between endangered FPM and their salmonid hosts – in addition or related to local adaptation – may be recovered through successful conservation programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The research protocol used in that survey does not require expensive equipment and can easily be adapted for Myanmar. In the same way, a study on a cheap and mobile pontoon‐based conservation method for determining mussel–host associations, tested on Margaritifera margaritifera (Linnaeus, 1758) and its fish host Salmo trutta Linnaeus, 1758 (Douda et al, 2020), illustrates another approach that could be used in Myanmar, especially in the absence of research infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies identifying patterns in host‐fish suitability are needed to determine adequate management units for mussel–host resources. New technical solutions may enable simpler and more frequent intraspecific host testing in the field and areas with inadequate laboratory infrastructure (Douda et al, 2020 ). This will also lead to a better appreciation of how short‐term benefits from fish and mussel captive breeding programs might be offset by long‐term impairment of mussel–fish relationships in the wild.…”
Section: Theme: Population Dynamicsmentioning
confidence: 99%